Final Report on the Hawaiʻi P-3 Evaluation - Zellman, Gail L. (Rand Corporation, 2015)
Results of a five-year evaluation of Hawai'i's P-3 initiative, which aimed to have every child reading at grade level by third grade, show students with more years of P-3 exposure were more likely to score proficient on the state reading test.